Masonry and render mortars with tyre rubber as aggregate: Fresh state rheology and hardened state performances. (10th June 2020) - Di Mundo, Rosa; Seara-Paz, Sindy; González-Fonteboa, Belén; Notarnicola, Michele
Highlights: Recycled Tyre rubber is mixed with sand as aggregate for masonry/render mortar. Mixing has been designed in order to not vary granulometry of the mixtures. With 20% rubber water penetration is minimized and strengths slightly depleted. Fresh state workability and thixotropy decrease as rubber content increases. Abstract: This work shows how it is possible to tailor cement-rubber composites suitable as renders and masonry mortars with a reduced liquid water absorption. Recycled tyre rubber is used as aggregate in mixture with siliceous sand and its content is tuned in order to limit depletion of mechanical properties and, at the same time, ensure a sufficiently massive utilization of this secondary raw material. An extended investigation of the properties both at the fresh and hardened state is conducted. We show that presence of rubber sensitively reduces fluidity (hence workability) of the mortar. In particular, rubber modifies rheological properties such as thixotropy and dynamic torque, while does not affect viscosity. Overall, the fresh state properties are compatible with the casting and application of these mortar typologies, even for the highest rubber content (20–25% by volume). This rubber content is shown to be sufficient to ensure, just after few days of curing, an almost complete abatement of water drop absorption, specific functionality of these novel and more sustainable mortars.